Exchange-Rate Variability, Real and Monetary Shocks, and the Degree of Capital Mobility Under Rational Expectations - Driskill, Robert; McCafferty, Stephen (Quarterly Journal of Economics, 1980)
Robert Driskill, Stephen McCafferty; Exchange-Rate Variability, Real and Monetary Shocks, and the Degree of Capital Mobility Under Rational Expectations, The Qu